Phthalimidine based fluorinated sulfonated poly(arylene ether sulfone)s copolymer proton exchange membranes - Mukherjee, Rajdeep; Mohanty, Aruna Kumar; Banerjee, Susanta; Komber, Hartmut; Voit, Brigitte (Journal of Membrane Science, 2013)
A series of phthalimidine based aromatic fluorinated sulfonated poly(arylene ether sulfone) (PAQSH-XX) copolymers were prepared by direct polycondensation reaction. The copolymer structures were confirmed by FTIR and NMR (1H, 13C, 19F) spectroscopy. The copolymers showed high molecular weight and tough membranes were obtained from their solution in N,N-dimethylacetamide (DMAc). The copolymers showed high thermal and oxidative stability and high mechanical properties depending upon their chemical compositions. Transmission electron microscopy (TEM) images of the membranes showed phase separated morphology with ionic cluster sizes from 2 to 17nm. The copolymers showed good dimensional stability and low water uptake values. Ion exchange capacity (IECW) of the copolymers was calculated from the monomer composition obtained from 1H NMR spectroscopy and determined by tritemetric methods. The proton conductivities of PAQSH-XX membranes increased with IECW value and temperature; a maximum value of 50mS/cm at 80°C for PAQSH-60 copolymer was achieved. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Fluorinated co-poly(arylene ether sulfone)s; Proton conductivity; Structure-property relationship